The influence of the Consumer Protection Act 68 of 2008 on the common law obligations of the seller vis-à-vis risk and duty to take care, eviction, and defects - Lotz, D.J. (Dirk Johannes) (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.